MASS DEMONSTRATIONS AND THE FALL OF THE SAP VOJVODINA REGIME IN 1988 (Heritage, 2020)
The main cause of demonstrations was Vojvodina leadership's persistent refusal to accept changes to the Constitution that would confirm the sovereignty of Serbia in its autonomous provinces. After Slobodan Milosevic rose to power, the Serbian authorities developed two different policies regarding autonomous provinces.  In case of Vojvodina, the main emphasis was on using the lack of democratic capacity and legitimacy of the leadership in Vojvodina, while leadership of Kosovo was the subject of party pressure through the League of Communists of Yugoslavia.Leadership of Vojvodina, which has been decisively and confidently rejecting any thought in which Vojvodina could be politically subordinated to the republic, was confused by the July and August demonstrations. In absence of finding an adequate response to the new situation, leadership remained passive, which ultimately led to complete paralysis of Vojvodina government.The confusion and passiveness of the main Vojvodina communists during the summer and autumn of 1988. indicates that demonstrations hit their weakest point – democratic capacity. It turned out that the stern attitude of Vojvodina Communists towards Serbia was not supported by the population of Vojvodina, and that the province government policy was not legitimate..Second key factor in the Anti-bureaucratic revolution in Vojvodina was the influence of media, which was controlled by the Serbian leader Slobodan Milosevic.The anti-bureaucratic revolution in Vojvodina represents a historical phenomenon of a unique kind, which at the same time contains the elements of the Revolutions of 1989, in which Eastern European regimes were down due to the lack of their own legitimacy and under the burst of the popular rebellion, as well as elements of the "Cultural Revolution" in China, when the most powerful man of the party used and manipulated national dissatisfaction in order to remove political opponents and reduce the influence of competitive fractions in the party.
Keywords: Socialist Autonomous Province of Vojvodina, Anti-bureaucratic revolution, Yugoslavia, Kosovo and Metohija.